Top-Up Individual Services On Fund Applications In Kota Langsa (Comparative Study Of Shafi`Iyyah And Malikiyyah) - Firdaus, Muhammad; Budi Juliandi; Nadia Ayuna (FEBI IAIN Langsa, 2023)
The use of digital money (e-money) is very common around us. It can be seen that many individual top-up services can make it easier for us to exchange cash for digital money, in this case, the author uses the DANA digital wallet as the object of research. This study aims to determine whether the mechanism for the top-up of individual services on the application of funds is by the sharf contract and the views of Syafi`iyyah and Malikiyyah on sharf transactions that are late or not cash. In this research, the writer uses the juridical-empirical research method. Based on interview data obtained from individual service top-up transactions, there are obstacles in terms of the network that can make top-up transactions require a waiting time of 2x24 working hours, from the analysis according to Syafi`iyyah and Malikiyyah, sharf transaction contracts must occur in cash, but Syafi` iyyah allows sharf transactions to occur slowly as long as the buyer and seller do not separate, on the contrary Malikiyyah requires sharf transactions to occur quickly even though the two are not separated, the transaction must be completed as quickly as possible.